Population Genomics and Demographic Sampling of the Ant-Plant Vachellia drepanolobium and Its Symbiotic Ants From Sites Across Its Range in East Africa - Boyle, John H.; Martins, Dino; Musili, Paul M.; Pierce, Naomi E. (Frontiers in Ecology and Evolution, 2019)
The association between the African ant plant, Vachellia drepanolobium, and the ants that inhabit it has provided insight into the boundaries between mutualism and parasitism, the response of symbioses to environmental perturbations, and the ecology of species coexistence. We use a landscape genomics approach at sites sampled throughout the range of this system in Kenya to investigate the demographics and genetic structure of the different partners in the association. We find that different species of ant associates of V. drepanolobium show striking differences in their spatial distribution throughout Kenya, and these differences are only partly correlated with abiotic factors. A comparison of the population structure of the host plant and its three obligately arboreal ant symbionts, Crematogaster mimosae, Crematogaster nigriceps, and Tetraponera penzigi, shows that the ants exhibit somewhat similar patterns of structure throughout each of their respective ranges, but that this does not correlate in any clear way with the respective genetic structure of the populations of their host plants. A lack of evidence for local coadaptation in this system suggests that all partners have evolved to cope with a wide variety of biotic and abiotic conditions.